Pengaruh Pendidikan, Pelatihan dan Penyuluhan Terhadap Partisipasi Anggota Koperasi Pondok Pesantren - Agus Eko Sujianto (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2012)
The purposes of this research are intended to measure the influence of education, Training and counseling simultaneously to the member participation of Koperasi Pondok Pesantren (Koppontren). Qualitative method was applied with the cross-section model. In organizing 320 person of respondent the writer applied multistage random sampling and each variable were measured with linear programming. Finally the finding of the research shows that education, training, and counseling simultaneously influence the members of Koppotren in Tulungagung regency.